Implementation of Balanced Scorecard to Achieve The Company's Strategic Objectives - Robertus Maria Bambang Gunawan (Eduvest - Journal of Universal Studies, 2024)
The company's strategic objectives play a vital role in directing the company towards the desired achievement and planning the steps to achieve it. Clarity of corporate objectives supported by commitment to them can lead to significant performance improvements, in contrast to providing objectives that are vague or too general. The process of achieving these goals involves monitoring through performance measurement. One effective performance measurement method is using the Balanced Scorecard, which combines financial and non-financial aspects of the company. The purpose of this study is to analyze the application of the Balanced Scorecard to achieve the company's strategic goals. The research method used is qualitative, with data collection techniques through literature studies. The collected data were then analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the use of Balanced Scorecard (BSC) can effectively assist the company in achieving its strategic goals. Good linkages between financial, customer, internal business, and growth and learning perspectives can produce optimal performance both in terms of financial and non-financial aspects for the company. The BSC approach focused on improving company performance not only encourages improvement in financial aspects, but also becomes the basis for evaluating the company's strategy to achieve continuous improvement.